1998
DOI: 10.1109/23.737672
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative /sup 131/I SPECT with triple energy window Compton scatter correction

Abstract: In this work accuracy of quantitative l 3 I I SPECT with triple energy window (TEW) scatter correction is evaluated by phantom measurements. The application is tumor imaging of B-cell lymphoma patients treated with l I radioimmunotherapy. The TEW method is a pixel by pixel correction where the scatter fraction in the photopeak window is estimated by linear interpolation between two adjacent narrow sub-windows.For the phantom measurements performed in this work the TEW estimate of scattered counts was close to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…Here is defined as the ratio of the background activity concentration in the cylindrical phantom over the activity concentration in the target. In contrast, in previous phantom measurements, we observed that the total count for a fixed-size spherical target changed when the level of the background activity changed [4]. Our images were reconstructed by a regularized algorithm (SAGE) without detector response [5], [6] and a fixed-size VoI determined from computed tomography (CT) was employed.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Here is defined as the ratio of the background activity concentration in the cylindrical phantom over the activity concentration in the target. In contrast, in previous phantom measurements, we observed that the total count for a fixed-size spherical target changed when the level of the background activity changed [4]. Our images were reconstructed by a regularized algorithm (SAGE) without detector response [5], [6] and a fixed-size VoI determined from computed tomography (CT) was employed.…”
Section: Introductionmentioning
confidence: 90%
“…For the calibration phantom with SAGE reconstruction, this transformation was final. It is the same procedure that was employed for a previous camera calibration with a high-energy collimator [4] and for processing patient data [10].…”
Section: F Ct-to-spect Registration and Voi Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Sinograms were corrected for scatter using standard triple energy window ͑TEW͒ correction. 26 After scatter subtraction, the data were reconstructed into 128ϫ 128 pixel images ͑3.67 mm pixel size͒ using standard MLEM ͑64 iterations͒ with attenuation correction as in Ref. 27.…”
Section: Iie2 Thorax Phantommentioning
confidence: 99%
“…The effective hole-length parameter Those planar images were later added together. Planar images were acquired with a 20%-width window around the 364 keV photopeak, and adjacent 10%-width windows for scatter correction using the triple-energy window (TEW) method [7], [8]. The estimated scatter events in the photopeak window calculated by TEW were about 5% of the total number of events in the photopeak window.…”
Section: B Crystal Efjiciency Calibrationmentioning
confidence: 99%